Room-temperature continuous-wave operation of membrane distributed-reflector laser. (20th October 2015) - Hiratani, Takuo; Inoue, Daisuke; Tomiyasu, Takahiro; Atsuji, Yuki; Fukuda, Kai; Amemiya, Tomohiro; Nishiyama, Nobuhiko; Arai, Shigehisa
Abstract: In this paper, we report on the first ever demonstration of a continuous-wave operation of an injection-type membrane distributed-reflector (DR) laser at room temperature. A threshold current of 250 µA was obtained with a stripe width of 0.7 µm, a DFB region length of 30 µm, and a DBR region length of 90 µm. An external differential quantum efficiency of 11% with a light output ratio between the front and the rear of 6.7 was obtained at the front waveguide.